Coping With Stillbirth Among Ultraorthodox Jewish Women. (July 2014) - Hamama-Raz, Yaira; Hartman, Hadas; Buchbinder, Eli
Stillbirth is a traumatic prenatal loss with personal, familial, and social implications. We explored the meaning of stillbirth for ultraorthodox Israeli women for whom grieving for prenatal loss derived from the power of faith. We conducted semistructured interviews with ten ultraorthodox women, ages 26 to 55, in a qualitative study that was focused on thematic content analysis and influenced by the phenomenological-hermeneutic tradition. The loss of the fetus was experienced as a test to the women's belief in God, and was perceived as a way to experience God's love. The women's faith became stronger and provided relief, calm, and confidence in God as benefactor. The meanings they attributed to their losses enabled them to move on. Findings are discussed in the context of research and theoretical literature on coping, bereavement, and mourning processes, and meaning for pregnancy-related losses. Awareness of ethnic meanings of stillbirth promotes implementation of culture-sensitive psychosocial interventions.